If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+6=10x+14
We move all terms to the left:
2x+6-(10x+14)=0
We get rid of parentheses
2x-10x-14+6=0
We add all the numbers together, and all the variables
-8x-8=0
We move all terms containing x to the left, all other terms to the right
-8x=8
x=8/-8
x=-1
| 2.3=x/2 | | 16c–9c=7 | | 5/m=10/100 | | -5x-97=-142 | | 10y+4y=-14 | | k/30=3/9 | | 4.1x+7=2.6x-2 | | 10/16=5/6x | | 4x=2(x+1)=3(x-1) | | -6(y-3y)+2=-3(3y-y)+4+17y | | (9x-3)(2x+4)=0 | | 25/100=5/j | | -3=1/2x+4 | | 1/2•(12f+30)=9 | | 3(y+5)=4(y-y) | | -3(x+4)+6=5(x+2)+5 | | .50•(12f+30)=9 | | X^2+4x+4=73 | | 18=-2x-76 | | 50x-3x+7=99+x | | 10/g=10/5 | | 120q-4q=8q | | 7y-3-2y=5+4y | | 16=4(x-1)-(x-8) | | 11=w/5+10 | | 15x4=26 | | 13v–12v=19 | | v/4-10=29 | | 3(y+5)=4(y+y) | | 1/2(8-6x)=94 | | 3y-4=11y+20 | | (y+9)²-(y-5)²=28 |